Positioning of the SCRAMBLED receptor requires UDP-Glc:sterol glucosyltransferase 80B1 in Arabidopsis roots - Victoria G. Pook (Nature Portfolio, 2017)
Abstract The biological function of sterol glucosides (SGs), the most abundant sterol derivatives in higher plants, remains uncertain. In an effort to improve our understanding of these membrane lipids we examined phenotypes exhibited by the roots of Arabidopsis (Arabidopsis thaliana) lines carrying insertions in the UDP-Glc:sterol glucosyltransferase genes, UGT80A2 and UGT80B1. We show that although ugt80A2 mutants exhibit significantly lower levels of total SGs they are morphologically indistinguishable from wild-type plants. In contrast, the roots of ugt80B1 mutants are only deficient in stigmasteryl glucosides but exhibit a significant reduction in root hairs. Sub-cellular investigations reveal that the plasma membrane cell fate regulator, SCRAMBLED (SCM), is mislocalized in ugt80B1 mutants, underscoring the aberrant root epidermal cell patterning. Live imaging of roots indicates that SCM:GFP is localized to the cytoplasm in a non cell type dependent manner instead of the hair (H) cell plasma membrane in these mutants. In addition, we provide evidence for the localization of the UGT80B1 enzyme in the plasma membrane. These data lend further support to the notion that deficiencies in specific SGs are sufficient to disrupt normal cell function and point to a possible role for SGs in cargo transport and/or protein targeting to the plasma membrane.